Vacuum system upgrade for extended Q-range small-angle neutron scattering diffractometer (EQ-SANS) at SNS - Stone, Christopher (MethodsX, 2016)
The Extended Q-range Small-angle Neutron Scattering Diffractometer (EQ-SANS) instrument at the spallation neutron source (SNS), Oak Ridge, Tennessee, incorporates a 69 m(3) detector vessel with a vacuum system which required an upgrade with respect to performance, ease of operation, and maintenance. The upgrade focused on improving pumping performance as well as optimizing system design to minimize opportunity for operational error. This upgrade provided the following practical contributions: • Reduced time required to evacuate from atmospheric pressure to 2 mTorr from 500 to 1000 min to 60–70 min; • Provided turn-key automated control with a multi-faceted interlock for personnel and machine safety.